The Influence of Implementation of Trainer Crimping Learning Media on Computer Learning Outcomes and Basic Networks at Vocational High School Muhammadiyah 1 Taman - Nugroho, Oktavianto Ashror; Astuti, Cindy Cahyaning (Belantika Pendidikan, 2023)
The background of this research is the large number of students who do not understand and do not understand the correct crimping technique, so the researchers provide a training or trainer for vocational school students, especially majoring in Computer and Network Engineering. The method used in this research is an experimental method which uses pretest and posttest questions as a reference for success in this study. Data collection in this study was taken from a class where the subjects taken were Basic Computers and Networks. The results of this study where the results of calculating the hypothesis show a rejection of H0, so it can be concluded that the results of this study influence or have an impact on the learning outcomes of vocational school students.